LINGUISTIC DIVERSITY AND LANGUAGE RIGHTS - Normatov Haydar Zafar o'g'li (Western European Studies, 2024)
This article explores the concepts of linguistic diversity and language rights, examining their importance in the preservation of cultural identity and social cohesion. The article delves into the theoretical frameworks and empirical studies on the subject, providing a comprehensive analysis of how linguistic diversity is managed globally and the challenges faced by minority languages. It also discusses the legal frameworks that support language rights and the methods used to study linguistic diversity.
Keywords: Linguistic diversity; language rights; cultural identity